2016
DOI: 10.1002/anie.201606065
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Biodegradable Organic–Inorganic Hybrids for Efficient Cell Penetration and Drug Delivery

Abstract: We report a comprehensive study on novel, highly efficient, and biodegradable hybrid molecular transporters. To this end, we designed a series of cell-penetrating, cube-octameric silsesquioxanes (COSS), and investigated cellular uptake by confocal microscopy and flow cytometry. A COSS with dense spatial arrangement of guanidinium groups displayed fast uptake kinetics and cell permeation at nanomolar concentrations in living HeLa cells. Efficient uptake was also observed in bacteria, yeasts, and archaea. The CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
8
0
2
Order By: Relevance
“…The other factor is the well-known high ability of POSS to penetrate cell membranes. 30 Both these properties of POSS-NH 2 $HCl-DOX system appear to interplay and lead to improved activity on co-delivery of POSS and DOX. These results can point to a useful and simple way of improving efficacy of chemotherapy also for other drug-POSS systems, provided they contain functional groups assuring such weak but efficient interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The other factor is the well-known high ability of POSS to penetrate cell membranes. 30 Both these properties of POSS-NH 2 $HCl-DOX system appear to interplay and lead to improved activity on co-delivery of POSS and DOX. These results can point to a useful and simple way of improving efficacy of chemotherapy also for other drug-POSS systems, provided they contain functional groups assuring such weak but efficient interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, POSS shows low toxicity and excellent biocompatibility. [ 75,76 ] These combined features have triggered an interest in the application of POSS structures in areas such as bioimaging [ 77–79 ] and nanomedicine. [ 80 ]…”
Section: Applications Of Poss As Photoluminescent Materialsmentioning
confidence: 99%
“…Arginine-rich peptides such as trans-activator of transcription or homeoprotein transcription factors appear in nature and thus are evolutionarily optimized in the presence of biological fluids. Recently, it was demonstrated that cubeoctameric silsesquioxanes 70 with similar positively charged ligands efficiently translocate through cell membranes.…”
Section: A Properties Of the Surrounding Mediamentioning
confidence: 99%